Perancangan Interior Coffee House di Surabaya - Gabriel Indra Purwanto; I Gusti Ngurah Ardana (Intra, 2016)
In this globalization era, the culture of drinking coffee has become a lifestyle in many region in Indonesia. This lifestyle has already expanded in Surabaya, but there hasn’t been a place provided with variety of facilities which interior is designed specifically to be representative as a place to express this lifestyle and also can be used as business opportunities which is definitely profitable. Therefore, interior design of Coffee Houseis proposed in a building designed by Ardhian W. located at MH. Thamrin 66b-68 and Imam Bonjol 117-123 Surabaya. The design was made based on data collection method by which in the results of the design will be strongly influenced by the process before. The design solution is processed based on fresh and pleasure concept, so that the interior design is able to present a fresh and pleasant atmosphere. The main facilities of this design are cafe, coffee strore, information and classroom as support facilities for workshop activity, exhibition in the form ofa gallery, lobby, receptionist, and office.Fresh atmosphere manifested through the arrangement of attractive design elements with a game of shapes, colors and materials. A pleasant atmosphere can be felt by creating an interior ambience that meets the needs of users as a whole, has durability value which ensures the robustness and security. This Coffee House design is expected to give knowledge, new atmosphere and exciting experience for the people in Surabaya.